Circulating Tumor DNA as a Predictive Marker of Recurrence for Patients With Stage II-III Breast Cancer Treated With Neoadjuvant Therapy - Lin, Po-Han; Wang, Ming-Yang; Lo, Chiao; Tsai, Li-Wei; Yen, Tzu-Chun; Huang, Thomas Yoyan; Huang, Wei-Chih; Yang, Karen; Chen, Chih-Kai; Fan, Sheng-Chih; Kuo, Sung-Hsin; Huang, Chiun-Sheng (Frontiers in Oncology, 2021)
Background: Patients with stage II to III breast cancer have a high recurrence rate. The early detection of recurrent breast cancer remains a major unmet need. Circulating tumor DNA (ctDNA) has been shown to be a marker to detect disease progression in metastatic breast cancer. We aimed to evaluate the prognostic value of ctDNA in the setting of neoadjuvant therapy (NAT). Methods: Plasma was sampled at the initial diagnosis (defined as before NAT) and after NAT and breast surgery (defined as after NAT). We extracted ctDNA from the plasma and performed deep sequencing of a target gene panel. The detection of alterations, such as mutations and copy number variations, were considered to indicate ctDNA positivity. Results: A total of 95 patients were enrolled in this study; 60 patients exhibited ctDNA positivity before NAT, and 31 patients had ctDNA positivity after NAT. A pathologic complete response (pCR) was observed in 13 patients, including one ER(+)Her2(-) patient, six Her2(+) patients and six triple-negative breast cancer (TNBC) patients. Among the entire cohort, multivariate analysis showed that an N3 classification and ctDNA positivity after NAT were independent risk factors that predicted recurrence (N3, hazard ratio (HR) 3.34, 95% confidence interval (CI) 1.26 – 8.87, p = 0.016; ctDNA, HR 4.29, 95% CI 2.06 – 8.92, p < 0.0001). The presence of ctDNA before NAT did not affect the rate of recurrence-free survival. For patients with Her2(+) or TNBC, non-pCR breast cancer patients were associated with a trend of higher recurrence (p = 0.105). Advanced nodal status and ctDNA positivity after NAT were significant risk factors for recurrence (N2 – 3, HR 3.753, 95% CI 1.146 – 12.297, p = 0.029; ctDNA, HR 3.123, 95% CI 1.139 – 8.564, p = 0.027). Two patients who achieved a pCR had ctDNA positivity after NAT; one TNBC patient had hepatic metastases six months after surgery, and one Her2(+) breast cancer patient had brain metastasis 13 months after surgery. Conclusions: This study suggested that the presence of ctDNA after NAT is a robust marker for predicting relapse in stage II to III breast cancer patients.